RETRACTED: In silico investigation of novel Plasmodium Falciparum glycogen synthase kinase (pfGSk3β) inhibitors for the treatment of malaria infection - Kassim Folorunsho Adebambo; Sara Otify (PLoS ONE, 2025)
Malaria, a parasitic disease, remains a major global health concern, with over 260 million cases reported worldwide in 2023. As resistance to current antimalarial drugs increases, the demand for ongoing research into new therapeutic targets and strategies grows. Glycogen synthase kinase (pfGSK3β) is a crucial enzyme involved in metabolic processes of the malaria parasite. In this research, an in silico study was conducted to explore this enzyme as a potential target for drug repurposing. A Python program was used to mine and extract data from the CHEMBL database, which yielded 53 potential GSK-3β inhibitors. Subsequent in silico studies included molecular docking, molecular dynamics simulations (MD, run at 100 ns on GROMACS 2023 1), and molecular mechanics Poisson-Boltzmann surface area (MMPBSA). In silico data analysis identified three potential drug molecules: S20-CHEMBLID 1910196 (4-[5-(6- hydroxy- 1H-indol-2- yl)pyridin-3- yl]benzonitrile), S39-CHEMBL ID 2321945 (2-(7- bromo- 2- hydroxy- 1H-indol-3-yl)-3- oxoindole- 6- carboxylic acid), and S56-CHEMBL ID 2321951 (methyl 2-(2- hydroxy-1H-indol-3-yl)-3-nitroso-1H-indole-5-carboxylate),which could inhibit pfgsk 3β. Compound S56 demonstrated better in silico performance than S1 – (3,6- diamino- 4-(2- chlorophenyl)thieno[2, 3- b] pyridine- 2, 5-,5-dicarbonitrile), the co-crystallised ligand in pfgsk 3 β used as a control. The binding affinities of S1 and S56 are- 7.1157074 (10 ligand interactions) and – 5.64057302 (12 ligand interactions), respectively. The MD runs yielded average root-mean-square deviations (RMSDs) of 4.5 nm for S1 and 1.0 nm for S56. Furthermore, the root mean square fluctuation (RMSF) of S1 showed greater fluctuation between 0–1000 atoms compared to S56. MMPBSA analysis revealed comparable total energies: S56 was −14.45 kj/mol and S1 was −13.03 kj/mol. An in silico toxicity study using Protox III indicated the possible toxicity of the repurposed compounds. In conclusion, we propose that molecules S39, S20, and S56 could be repurposed as potential anti-malaria drugs.